Sistema de TI para gestão condominial - Kanashiro, Gílson Maekawa (2011)
This work presents a boarding of the question of coordination of activities under the point of view of a condominium management software. Of the author's experience, ex-condominium syndic, it focus on who manages, aiming flexibility and practice. It presents aspects of the condominium management. As results, research brings a simplified management tool that was developed to help on activities tracking.